Analisis Hubungan Zona Nilai Tanah Terhadap Keterdekatan Fasilitas Umum di Kota Bandung Menggunakan Pendekatan Sistem Informasi Geografis (SIG) dan Statistik - Sukawati, Maudi Nabila; Zavier Hidayat, Muhammad Akhdan; Ukasha, Muhammad Gala; Fadhlurrahman, Muhammad Shidqi; Rahmat, Nailla Alifia; Rahmadani, Nova Analia; Wardiyah, Mia Lasmi (Melati Institute, 2024)
Land Value Zones (ZNT) are boundaries with relatively similar land values. ZNT is important for local planning and policy. Land value is influenced by physical, accessibility and social factors, with social factors being the most significant. The creation of ZNT maps uses the integration of spatial and non-spatial data with geographic information systems (GIS). Previous methods paid little attention to social factors, which can determine up to 43% of land value. This study will examine the relationship between ZNT and proximity to social factors and represented by public facilities using GIS analysis and correlation tests. Results show that there is an inverse relationship between land value and proximity to public facilities. The correlation coefficient showed a value of -0.536. In addition, this study also shows an indication that the farther the land is from the railroad, the more expensive the land. Then the closer the land is to the road, the higher the land price. Translated with DeepL.com (free version)